2002
DOI: 10.1097/00005373-200201000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Review of Severe Pediatric Trauma in Eastern Ontario: A Descriptive Analysis

Abstract: Research efforts and activities to prevent severe pediatric trauma in our region should focus on road safety, protection from head injuries, avoidance of falls, and prevention of child abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
24
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 7 publications
9
24
0
2
Order By: Relevance
“…Several studies have reported the head region as the most commonly affected body system. [9][10][11][12][13] The reason for the high frequency of head injury following falls in children can be explained by their higher head/body ratio compared with adults, which makes landing on their heads more likely. 7 12 Fractures of the extremities in our study had a frequency of 14.5%, which put the second place for frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the head region as the most commonly affected body system. [9][10][11][12][13] The reason for the high frequency of head injury following falls in children can be explained by their higher head/body ratio compared with adults, which makes landing on their heads more likely. 7 12 Fractures of the extremities in our study had a frequency of 14.5%, which put the second place for frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] An important role of any trauma centre is to study the frequency, distribution, cause, and pattern of its trauma population and to compare these data with other trauma centres, in order to develop strategies to prevent injuries, which are applicable regionally and locally. [8][9][10] Several trauma scoring systems have been developed to measure the severity of the injury, and to analyse its impact on morbidity and mortality for trauma research. The most common scoring systems used include the Glasgow Coma Scale (GCS), 11 Revised Trauma Score, 12 Pediatric Trauma Score (PTS), 13 Injury Severity Score (ISS), 14 and the Trauma and Injury Severity Score.…”
mentioning
confidence: 99%
“…20 A prior Canadian analysis of severe pediatric trauma in Ontario determined that sports were responsible for 5% of trauma cases admitted to hospital over a four-year period. 21 Unlike this prior study from Ontario, we examined injury severity and patient outcomes by type of activity, and we included cycling as a sport/recreational activity, since it has a corresponding CIHI Sport & Recreation Code in the NSTR. Our results agree with Canadian data from CIHI, showing that cycling injuries are the most common injury from summer sport and recreational activity, with males aged 10-14 years hospitalized most frequently.…”
Section: Discussionmentioning
confidence: 99%
“…This peculiarly occurs from unguarded rooftops while the child is playing. However, Osmond[4] from Canada cites motor accidents as the most common cause. The most common lesion seen on CT scan was an EDH, whereas Mahapatra reports contusion as the most common.…”
mentioning
confidence: 99%